Human herpesviruses-encoded dUTPases: a family of proteins that modulate dendritic cell function and innate immunity - Ariza, Maria Eugenia; Glaser, Ronald; Williams, Marshall V. (Frontiers in Microbiology, 2014)
We have previously shown that Epstein-Barr virus (EBV)-encoded dUTPase can modulate innate immune responses through the activation of TLR2 and NF-kappaB signaling. However, whether this novel immune function of the dUTPase is specific for EBV or a common property of the Herpesviridae family is not known. In this study, we demonstrate that the purified viral dUTPases encoded by herpes simplex virus type 2 (HSV-2), human herpesvirus 6A (HHV-6A), human herpesvirus 8 (HHV-8) and varicella-zoster virus (VZV) differentially activated NF-kappaB through ligation of TLR2/TLR1 heterodimers. Furthermore, activation of NF-kappaB by the viral dUTPases was inhibited by anti-TLR2 blocking antibodies (Abs) and the over-expression of dominant negative constructs of TLR2, lacking the TIR domain, and MyD88 in human embryonic kidney 293 cells expressing TLR2/TLR1. In addition, treatment of human dendritic cells and PBMCs with the herpesviruses-encoded dUTPases from HSV-2, HHV-6A, HHV-8 and VZV resulted in the secretion of the inflammatory cytokines IL-1 beta, IL-6, IL-8, IL-12, TNF-alpha, IL-10 and IFN-gamma. Interestingly, blocking experiments revealed that the anti-TLR2 Ab significantly reduced the secretion of cytokines by the various herpesviruses-encoded dUTPases (p<0.05). To our knowledge, this is the first report demonstrating that a nonstructural protein encoded by herpesviruses HHV-6A, HHV-8, VZV and to a lesser extent HSV-2 is a pathogen-associated molecular pattern. Our results reveal a novel function of the virus-encoded dUTPases, which may be important to the pathophysiology of diseases caused by these viruses. More importantly, this study demonstrates that the immunomodulatory functions of dUTPases are a common property of the Herpesviridae family and thus, the dUTPase could be a potential target for the development of novel therapeutic agents against infections caused by these herpesviruses.